Research Joint Ventures, Licensing, and Industrial Policy - Cuihong Fan; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper reconsiders the explanation of R&D subsidies by Spencer and Brander (1983) and others by allowing firms to license their innovations and to pool their R&D investments. We show that in equilibrium R&D joint ventures are formed and licensing occurs in a way that eliminates the strategic benefits of R&D investment in the export oligopoly game. Nevertheless, national governments are driven to subsidize their own national firms in order to increase their strength in the joint venture bargaining game. Therefore, our analysis suggests an alternative explanation of the observed proliferation of R&D subsidies.
urn:nbn:de:bvb:19-epub-13462-5
Keywords: L13; O34; 330; patent licensing; industrial organization; R&D subsidies; research joint ventures; innovation policy